Features of ambulatory and stationary treatment of patients with endometriosis - Tat'iana A. Oboskalova; Evgenii Yu. Gluhov; Irina I. Astryuhina (IP Berlin A.V., 2020)
Background. Most common clinical manifestations of endometriosis (N80) include pelvic pain and infertility, while adenomyosis is associated with abnormal uterine bleeding. At present, approach to the treatment of endometriosis has been revised towards shifting surgery to the second-line therapy; medications are considered as the first-line therapy: gonadotropin releasing hormone agonists, progestogens, aromatase inhibitors. Aim. Comparison of clinical and anamnestic characteristics and therapeutic procedures in women who were treated on an outpatient basis and those who were hospitalized and underwent surgical intervention. Materials and methods. Clinical-anamnestic and morphological characteristics were studied in two groups of women: 1st group (n=27) received drug therapy, 2nd group (n=28) underwent surgical intervention. Results and discussion. In the 1st group, 25.9% of patients received microdosed combined oral contraceptives which contain dienogest as a progestogen component, 44.4% of patients received monotherapy with dienogest, and 22.2% of patients received dydrogesterone in a prolonged mode. In the 2nd group, 39 foci of endometriosis, isolated and in a combination of various loci, were revealed during surgery, of which 30.8% were ovarian cysts, 10.2% were foci on the sacro-uterine ligaments, 23.1% were on the pelvis peritoneum. Surgical approach was determined by the urgency of intervention, an expect localization of endometriosis foci, a comorbidity of endometriosis with another pathology of the internal genitalia, 82.1% of surgery were performed by laparoscopic approach. Conclusions. The choice of treatment method depends on the severity of symptoms, the severity of endometriosis, the woman age and her reproductive intentions. When choosing a surgical treatment, one should be guided not only by the need for the most radical removal of endometriosis foci, but also should consider a surgical approach to minimize discomfort and provide a good quality of life after surgery. A three-stage model for the management of patients with endometriosis is proposed, which includes an assessment of treatment effectiveness and the need to develop a rehabilitation program.